Wage Differences and Personal Workers’ Characteristics: An Analysis of Economic and Sociological Approaches - Татьяна Львовна Серикова (Journal of Economic Sociology, 2010)
The paper concentrates on the advantages and disadvantages of economic approaches to the wage differences explanations based on the human capital theory (the impact of the education, training, professional experience), on the economic theories focusing on the personal differences between people (differences in abilities and possibilities). Alternative sociological approaches (to social inequality and its effect on the wage differences in accordance with personal characteristics) are also in the focus of the paper. The author implies the empirical analysis of value changes to education and the influence of the employees’ quality difference on the wage distribution in Russia. The analysis is based on the sociological project «The Strategies of the Economic Survival of the Population in the Contemporary Russia».